The effect of post-activation potentiation on performance according to circadian rhythm in young athletes - Demirtaş, Canan Fikri; Akbulut, Taner; Çinar, Vedat; Avcu, Emsal Çağla; Migliaccio, Gian Mario; Beltrami, Gianfranco (Pensiero Scientifico Editore, 2025)
Background. The interaction between circadian rhythm and post-activation potentiation (PAP) - a phenomenon that causes temporary increases in muscle strength and performance following intense muscle contractions - is crucial for understanding daily variations in athletic performance. Methods. Fourteen male athletes voluntarily participated in a crossover design study. Athletes underwent both control and PAP interventions at different times of the day. Performance measurements included vertical jump, standing long jump, T-drill agility test, and 5-10 m sprint tests. Results. No significant differences were observed in standing long jump and vertical jump performances across different times of day or warm-up dependent changes were found in both 5 and 10 m sprint performances between warm-up practices (p<0.05). Agility performance showed significant variations according to time of day (p<0.05). Conclusions. Athletic performance metrics may vary according to circadian rhythm, with PAP potentially contributing to these variations. The findings suggest that the effectiveness of PAP interventions might be influenced by the time of the day they performed.
Keywords: Pap; circadian rhythm; warm-up; performance